Fluorine coating for improved chamber performance
By depositing metal fluoride protective coatings on the surface of semiconductor processing chamber components, the problems of particle deposition, deposition rate drift and corrosion uniformity caused by high temperature and high energy plasma and corrosive gases are solved, and higher processing stability and equipment life are achieved.
Patent Information
- Application Number
- JP2023504270
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-03
- Filing Date
- 2021-08-02
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2041-08-02
AI Technical Summary
During semiconductor processing, high temperature and high energy plasma and corrosive gases cause the reaction of the chamber components on the surface, producing high volatile gases, resulting in particle deposition, deposition rate drift and corrosion uniformity decrease.
Using metal fluoride as the protective coating, protective coating is deposited on the surface of chamber components through technologies such as atomic layer deposition (ALD), chemical gas deposition (CVD), electron beam ion assisted deposition (EB-IAD), to reduce reaction with plasma and corrosive gases.
Effectively reduces particle deposition and deposition rate drift, improves film and corrosion uniformity, and extends the service life of chamber components.
Smart Images

Figure 0007669471000001 
Figure 0007669471000002 
Figure 0007669471000003
Abstract
Description
[Technical field]
[0001]
[0001] Embodiments of the present disclosure relate to articles, coated chamber parts, methods for coating chamber parts, methods for reducing or removing particles, methods for reducing deposition rate drift or etch rate drift, and methods for improving film uniformity or etch uniformity in semiconductor processing chambers. [Background technology]
[0002] Various semiconductor manufacturing processes use high temperatures, high energy plasmas (such as remote and direct fluorine plasmas, such as NF3, CF4), mixtures of corrosive gases, high stresses, and combinations thereof. Under these extreme conditions, the plasma and corrosive gases react with the materials of the components in the chamber, causing the formation of high vapor pressure gases (e.g., AlF x ) can occur. Such gases can easily sublimate and deposit on other parts in the chamber. In subsequent steps, the deposited material can break off as particles from other parts and fall onto the wafer, creating defects. Such reactions can also cause problems such as deposition rate drift, etch rate drift, poor film uniformity, and poor etch uniformity. It is beneficial to reduce these defects with a low volatility coating on the reactants to limit the sublimation and / or deposition of the reactants on parts in the chamber. Summary of the Invention
[0003]
[0003] Described in embodiments herein is a semiconductor chamber component that includes a substrate and a protective coating deposited on a non-roughened surface of the substrate. In embodiments, the protective coating is an M1 x F w , M1 x M2 y F w and M1 x M2 y M3 z F wThe metal fluoride includes at least one metal fluoride having a formula selected from the group consisting of: x F w In an embodiment having the formula M1, x is 1 and w ranges from 1 to 3. x M2 y F w In an embodiment having the formula M1, x ranges from 0.1 to 1, y ranges from 0.1 to 1, and w ranges from 1 to 3. x M2 y M3 z F w In an embodiment, x ranges from 0.1 to 1, y ranges from 0.1 to 1, z ranges from 0.1 to 1, and w ranges from 1 to 3. In an embodiment, at least one of M1, M2, or M3 comprises magnesium or lanthanum.
[0004]
[0004] Described in embodiments herein is a method for reducing particles during processing in a semiconductor processing chamber. The method includes depositing a protective coating on a non-roughened surface of a substrate by atomic layer deposition (ALD), chemical vapor deposition (CVD), electron beam ion assisted deposition (EB-IAD), or physical vapor deposition (PVD). In embodiments, the protective coating is an M1 x F w , M1 x M2 y F w and M1 x M2 y M3 z F w The metal fluoride includes at least one metal fluoride having a formula selected from the group consisting of: x F w In an embodiment having the formula M1, x is 1 and w ranges from 1 to 3. x M2 y F w In an embodiment having the formula M1, x ranges from 0.1 to 1, y ranges from 0.1 to 1, and w ranges from 1 to 3. x M2 y M3 z F wIn an embodiment, x ranges from 0.1 to 1, y ranges from 0.1 to 1, z ranges from 0.1 to 1, and w ranges from 1 to 3. In an embodiment, at least one of M1, M2, or M3 comprises magnesium or lanthanum.
[0005]
[0005] Described in embodiments herein is a method for coating a surface of a substrate using atomic layer deposition (ALD). In embodiments, the method includes depositing a first adsorbed layer on the surface of the substrate by pulsing one or more metal precursors of M1, M2, M3, or combinations thereof into an ALD processing chamber. In embodiments, the method includes depositing a first adsorbed layer on the surface of the substrate by pulsing one or more metal precursors of M1, M2, M3, or combinations thereof into an ALD processing chamber. x F w , M1 x M2 y F w and M1 x M2 y M3 z F w and introducing a fluorine component into the ALD processing chamber to form at least one metal fluoride having a formula selected from the group consisting of: x F w In an embodiment having the formula M1, x is 1 and w ranges from 1 to 3. x M2 y F w In an embodiment having the formula M1, x ranges from 0.1 to 1, y ranges from 0.1 to 1, and w ranges from 1 to 3. x M2 y M3 z F w In an embodiment, x ranges from 0.1 to 1, y ranges from 0.1 to 1, z ranges from 0.1 to 1, and w ranges from 1 to 3. In an embodiment, at least one of M1, M2, or M3 comprises magnesium or lanthanum.
[0006]
[0006] The present disclosure is illustrated by way of example, and not by way of limitation, in the figures of the accompanying drawings in which like references indicate like elements. It should be noted that different references to "a" or "one" embodiment in the present disclosure are not necessarily references to the same embodiment, and such references mean at least one. [Brief description of the drawings]
[0007] [Figure 1] 1 is a cross-sectional view of a processing chamber. [Figures 2A-2D]
[0008] 2A-D are cross-sectional views of articles coated with various protective coatings, according to embodiments. [Diagram 3]
[0009] 1 illustrates a method for reducing particles during processing in a semiconductor processing chamber, according to an embodiment. [Figure 4A]
[0010] 1 illustrates a co-dosing or co-deposition mechanism applicable to atomic layer deposition (ALD) techniques that may be utilized to coat an article, according to certain embodiments. [Figure 4B]
[0011] FIG. 1 illustrates a sequential deposition mechanism applicable to an ALD technique that may be utilized to coat an article, according to an embodiment. [Diagram 5]
[0012] 1 illustrates an exemplary chemical vapor deposition (CVD) system that may be utilized to coat an article, according to an embodiment. [Figure 6]
[0013] 1 illustrates an exemplary physical vapor deposition (PVD) system that can be utilized to coat an article, according to an embodiment. [Figure 7A-7B]
[0014] 1 illustrates an exemplary electron beam ion-assisted deposition (EB-IAD) setup that may be utilized to coat an article, according to an embodiment. [Figure 8A]
[0015] FIG. 1 shows a cross-sectional view of an article coated with a protective coating deposited by ALD according to an embodiment, as viewed by scanning electron microscope (SEM) at 100 nm scale. [Figure 8B]
[0016] 8B shows an energy dispersive X-ray spectroscopy (EDS) line scan of the protective coating observed in FIG. 8A. [Figure 9A]
[0017] FIG. 1 shows a cross-sectional view of an article coated with an adhesion layer and a protective coating deposited by ALD according to an embodiment, as viewed by scanning electron microscope (SEM) at a 200 nm scale. [Figure 9B]
[0018] FIG. 9B shows an EDS line scan of the protective coating observed in FIG. 9A. [Fig. 9C1-9C3]
[0019] C1, C2, and C3 show cross-sectional views of the protective coating observed in Figure 9A viewed by scanning electron microscopy (SEM) at a 100 nm scale, showing the uniformity of the coating thickness and composition, except for the surface of the coating where nano-roughness is observed. [Figure 10A1-10A3]
[0020] 10A-1 show cross-sectional views of an article coated with a multilayer lamellar protective coating deposited by ALD according to an embodiment, as viewed by SEM at the 200 nm scale (FIG. 10A1), 100 nm scale (FIG. 10A2), and 20 nm scale (FIG. 10A3). [Figure 10B]
[0021] 10A, 10A2, and 10A3 show EDS line scans of the protective coatings observed in FIG. [Fig. 11A1-11A3]
[0022] 11A-1 show cross-sectional views of an article coated with another multilayer lamellar protective coating deposited by ALD according to an embodiment, as viewed by SEM at a 200 nm scale (FIG. 11A1), a 100 nm scale (FIG. 11A2), and a 20 nm scale (FIG. 11A3). [Figure 11B]
[0023] 11A1, 11A2, and 11A3 show EDS line scans of the protective coating observed in FIG. [Fig. 12A1-12D2]
[0024] 1A-1D show cross-sectional views of an article coated with a protective coating deposited by electron beam ion-assisted deposition (EB-IAD) at different EB-IAD deposition parameters according to one embodiment, as viewed under an SEM at different scales. [Figure 13]
[0025] 1 shows a cross-sectional view of an article coated with an adhesion layer and a protective coating deposited by EB-IAD according to an embodiment, as viewed by SEM at 0.2 μm scale. [Figure 14]
[0026] 1 shows an EDS line scan of a protective coating deposited by EB-IAD on a front side of a wafer compared to a back side of the wafer after the wafer was subjected to an aggressive cleaning test, illustrating the chemical stability of the coating composition, according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008]
[0027] Embodiments described herein encompass articles, coated chamber parts, methods of coating chamber parts, methods of reducing or removing particles from a semiconductor processing chamber, methods of reducing deposition rate drift or etch rate drift in a semiconductor processing chamber, and methods of improving film uniformity or etch uniformity on wafers processed in a semiconductor processing chamber.
[0009]
[0028] In an embodiment, the coated semiconductor chamber part includes a substrate and a protective coating deposited on a surface of the substrate. Exemplary substrates having surfaces that can be coated with the protective coatings described herein include, but are not limited to, semiconductor chamber parts located in the upper portion of a processing chamber (e.g., showerheads, faceplates, liners, electrostatic chucks, edge rings, blocker plates), as well as semiconductor chamber parts located in the lower portion of a processing chamber (e.g., sleeves, lower liners, bellows, gas boxes). Certain semiconductor process chamber parts that can be coated with the protective coatings described herein can have high aspect ratio portions, and the surfaces of the high aspect ratio portions can be coated with the protective coatings described herein.
[0010]
[0029] The protective coating described herein isx F w , M1 x M2 y F w and M1 x M2 y M3 z F w a) the metal fluoride formula is M1 x F w where x is 1 and w is in the range of 1 to 3, and b) the formula of the metal fluoride is M1 x M2 y F w where x is in the range of 0.1 to 1, y is in the range of 0.1 to 1, and w is in the range of 1 to 3; and c) the metal fluoride formula is M1 x M2 y M3 z F w where x ranges from 0.1 to 1, y ranges from 0.1 to 1, z ranges from 0.1 to 1, and w ranges from 1 to 3. At least one of M1, M2, or M3 is magnesium or lanthanum. Each of M1, M2, and M3 represents a different metal, such as, but not limited to, magnesium, yttrium, aluminum, or a lanthanide. Without being limited thereto, it is believed that magnesium-containing metal fluorides and lanthanum-containing metal fluorides are suitable candidates for protective coatings because the reaction product of a magnesium-containing or lanthanum-containing fluoride with a fluorine-containing plasma is believed to have a lower vapor pressure than the vapor pressure of the reaction product of a substrate material with a fluorine-containing plasma.
[0011]
[0030] Exemplary protective coatings as defined above include Mg x F w , La x F w , Y x Mg y F w , Y x La y F w , La x Mg y F w Or Y x Mg y La zF w It may include at least one of the following:
[0012]
[0031] In certain embodiments, the metal fluoride protective coatings described herein can also be "low volatility coatings." As used herein, the term "low volatility coating" refers to a coating that, when exposed to a high temperature plasma, reacts with the plasma to produce compounds or metal compounds (such as metal fluorides) that have a low vapor pressure. In embodiments, the vapor pressure of the low vapor pressure metal compound is at least an order of magnitude lower than the vapor pressure of the gas produced when the plasma reacts with an uncoated chamber part material in the same environment (e.g., under the same conditions and using the same measurement method).
[0013]
[0032] Exemplary materials for the substrate include, but are not limited to, metals or ceramics, such as aluminum alloys, AlN, Al2O3, stainless steel, nickel, nickel-chromium alloys, and the like.
[0014]
[0033] In one example, the substrate can include an aluminum-based component (such as aluminum, an aluminum alloy, or Al2O3). Upon exposure of the aluminum-based component to a fluorine-containing plasma at temperatures between 400° C. and 1000° C., the aluminum of the aluminum-based component reacts with the fluorine to form highly volatile AlF due to their high vapor pressure in the illustrated temperature range. x It may form seeds, e.g., Mg x F w Coating aluminum-based components with a protective coating containing Mg x F w The reaction of the magnesium component in the coating with a fluorine-containing plasma is shown to be AlF x They form reaction products that have a lower vapor pressure than the seeds and are less likely to sublime and deposit elsewhere in the processing chamber, thereby reducing the number of particles produced.
[0015]
[0034] Various coating structures are contemplated for the protective coating described herein. In one embodiment, the protective coating can be deposited directly on the bare surface of the substrate. In another embodiment, an adhesion layer can be deposited on the surface of the substrate, and the metal fluoride-containing protective coating can be deposited on the adhesion layer. The adhesion layer can also be configured to improve the adhesive strength between the surface of the substrate and the metal fluoride-containing protective coating. The adhesion layer can also be configured to relieve stress by having a coefficient of thermal expansion (CTE) value, for example, between the CTE of the protective coating and the CTE of the substrate, to reduce potential CTE mismatch between the substrate and the protective coating. The adhesion layer can also be configured as a diffusion barrier layer to prevent fluorine-containing species (such as fluorine radicals) from diffusing from the processing environment in the semiconductor processing chamber or from the fluorine-containing protective coating all the way to the substrate below. In certain embodiments, the adhesion layer can be amorphous, such as amorphous alumina, or amorphous yttrium aluminum garnet (YAG).
[0016]
[0035] Another suitable coating structure of the fluorine-containing protective coating can be an uninterrupted continuous growth crystalline phase with a rough surface. In certain embodiments, the protective coating is designed with a specific roughness on the top surface of the coating so that if particles are generated during processing, the particles will mainly adhere to the coating of the semiconductor chamber parts and not to the wafer being processed. One method of roughening the top surface of the coating is to deblast the coating. Deblasting is commonly used, but is less preferred because particles generated during deblasting can shed at high processing temperatures and contaminate the wafer being processed in the processing chamber. In the present disclosure, the crystallinity of Mg-based metal fluorides and / or La-based metal fluorides is utilized to continuously grow crystalline Mg-based metal fluorides and / or crystalline La-based metal fluorides while controlling the nanoscale surface topography to achieve the target roughness. In other words, in the present disclosure, the nano- or micro-roughness of the top surface of the metal fluoride-containing protective coating can be tailored by controlling the deposition of the crystalline phase of the metal fluorides that form the protective coating. The nano- or micro-roughness of the resulting top surface of the metal fluoride-containing protective coating may be suitable for promoting adhesion of particles that may be generated during processing in a semiconductor processing chamber. In certain embodiments, the roughness of the top surface of the protective coating is in the range of about 0.1 microinches to about 200 microinches, about 0.5 microinches to about 50 microinches, about 2 microinches to about 30 microinches, about 5 microinches to about 20 microinches, about 75 microinches to about 150 microinches, or about 30 microinches to about 100 microinches, or any subrange or single value therein.
[0017]
[0036] Yet another coating structure suitable for the fluorine-containing protective coating is a multi-layer structure, such as a lamellar structure. The multi-layer structure may, for example, include multiple alternating layers of amorphous and crystalline layers. In one exemplary embodiment, the lamellar structure may include alternating layers of amorphous Al2O3 and crystalline MgF2.
[0018]
[0037] A variety of deposition techniques may be utilized to coat the surface of the substrate depending on the coating's structure, target thickness, porosity, uniformity, compatibility, composition, application, etc. Suitable deposition techniques include atomic layer deposition (ALD), chemical vapor deposition (CVD), electron beam ion assisted deposition (EB-IAD), or physical vapor deposition (PVD).
[0019]
[0038] ALD and CVD techniques are non-line of sight deposition techniques and are suitable for depositing thin protective coatings. Thinner protective coatings may be suitable for applications where the protective coating should remain substantially unaffected (e.g., unchanged within about ±10%) the properties (e.g., thermal properties) of the underlying components. For example, thinner coatings may be suitable for heaters to provide fluorine protection without significantly affecting the thermal properties (e.g., thermal conductivity, heat capacity, temperature) of the underlying heater. PVD and EB-IAD are line of sight techniques and may be suitable for applications where thicker coatings than those deposited by ALD or CVD are acceptable.
[0020]
[0039] In one embodiment, ALD is advantageously used to deposit the protective coatings described herein due to the high density, low porosity (0%), high uniformity, high conformality, ability to coat high aspect ratio surfaces and complex three-dimensional shapes, low defect rate, and high tenability associated with the ALD technique. Unlike ALD, methods such as thermal spraying, sputtering, plasma spraying, or evaporation techniques generally cannot deposit conformal, uniform coatings on the complex shapes of parts with the low defect density of ALD coatings. With the ALD technique, the crystalline metal fluoride containing protective coatings can be deposited sequentially in a controlled manner to achieve a target micro- or nano-roughness that promotes particle adhesion. With the ALD technique, it is also possible to achieve a multi-layered lamellar structure with alternating amorphous and crystalline layers. Coatings deposited by ALD have a uniform thickness with less than ±20% thickness variation, or less than ±10% thickness variation, or less than ±5% thickness variation, or lower thickness variation when comparing the thickness of the coating at one location to the thickness of the coating at another location, or when quantifying the standard deviation of multiple thickness values obtained from a protective coating from multiple locations.
[0021]
[0040] ALD allows for controlled, self-limiting deposition of materials by chemical reaction with the surface of an article. In addition to being a conformal, uniform process, ALD is capable of forming very thin films. A typical reaction cycle of an ALD process begins with one or more precursors flooding into the ALD chamber and adsorbing on the surface of the substrate (including the surface of the pore walls within the substrate). In the present disclosure, the precursors may be one or more metal precursors of M1, M2, M3, or combinations thereof. Excess precursors are then flushed from the ALD chamber before one or more reactants are introduced into the ALD chamber and subsequently flushed out. In the present disclosure, the reactants may be fluorine-containing reactants in one embodiment, or oxygen-containing reactants that subsequently undergo fluorination in another embodiment. In the case of ALD, the final thickness of the material depends on the number of reaction cycles that are performed, as each reaction cycle grows a layer of a particular thickness, which may be an atomic layer or a portion of an atomic layer.
[0022]
[0041] ALD techniques can deposit thin layers of material at relatively low temperatures (e.g., about 25 °C to about 350 °C), so they do not damage or deform the materials of the chamber components. In addition, ALD techniques can also deposit layers of material within complex features of a component (such as high aspect ratio features). In addition, ALD techniques generally produce coatings that are relatively thin (i.e., 1 μm or less) and non-porous (i.e., no pinholes), which can prevent the formation of cracks during deposition.
[0023]
[0042] As discussed with respect to ALD techniques, in certain embodiments, the metal fluoride comprising the protective coating is a metal oxide species (e.g., M x M2 y M3 z O a) (among other steps). Thus, in certain embodiments, the protective coating can contain some amount of oxygen atoms, such as up to 40 atomic % oxygen. In certain embodiments, the amount of oxygen can be reduced to single digit atomic % (e.g., less than 10 atomic %) or eliminated entirely (e.g., 0 atomic % oxygen).
[0024]
[0043] The atomic percentages of the various components (i.e., M1, M2, M3, F, and optionally O) of the metal fluoride protective coating can be adjusted based on the intended application and intended properties of the protective coating. For example, the composition can be adjusted to control and / or achieve a target vapor pressure of the coating. Thus, in certain embodiments, the disclosure is directed to a method for adjusting / controlling the vapor pressure of the protective coating. In another example, the composition can be adjusted to modify / adjust / enhance the fluorine resistance of the protective coating. Thus, in certain embodiments, the disclosure is directed to a method for modifying / adjusting / enhancing the fluorine resistance of the protective coating. In yet another example, the composition of the coating can be adjusted to control the phase (e.g., amorphous or crystalline) and structure of the protective coating. Thus, in certain embodiments, the disclosure is directed to a method for controlling the phase and / or structure of the protective coating.
[0025]
[0044] For thicker protective coatings (e.g., micrometer scale), techniques such as EB-IAD and PVD can be beneficially utilized. These techniques, like ALD, can be utilized to deposit protective coatings over adhesion layers, continuous single protective layers, and multi-layered protective coatings. EB-IAD can be an advantageous alternative to deposition techniques such as plasma spraying. Plasma spraying techniques rely on deblasting to improve the surface roughness of the underlying substrate and promote adhesion of the coating onto the underlying substrate. Deblasting to roughen the underlying substrate encourages the underlying substrate to become filled with microcracks. In contrast, deblasting is not part of the EB-IAD deposition process. Thus, EB-IAD coated substrates do not become rough and do not develop as many microcracks as plasma spray coated substrates.
[0026]
[0045] The metal fluoride protective coatings described herein (containing at least a Mg or La component) are fluorine-containing species (e.g., AlF x ) have a low evaporation rate (low vapor pressure) compared to typical reaction products of the substrate with metal fluoride. ) In addition, because the metal fluoride protective coatings are already fluorinated, they are expected to be more fluorine resistant (i.e., form a better barrier against the diffusion of fluorine) than the underlying substrate or compared to the same metal in the oxide form. They are also expected to be more fluorine resistant than the native oxide layer of the underlying substrate material.
[0027]
[0046] FIG. 1 is a cross-sectional view of a semiconductor processing chamber 100 having one or more chamber parts coated with a protective coating according to an embodiment. The processing chamber 100 can be used for processes in which a corrosive plasma environment having plasma processing conditions is provided. For example, the processing chamber 100 can be a chamber for a plasma etcher or plasma etch reactor, a plasma cleaner, a plasma enhanced CVD or ALD reactor, etc. Examples of chamber parts that can include a protective coating include chamber parts that are at risk of exposure to fluorine chemistry and corrosive environments during processing. These may be heaters, electrostatic chucks, faceplates, showerheads, liners, blocker plates, gas panels, edge rings, bellows, etc., either at the top or bottom of the chamber. The protective coatings, detailed below, can be applied by either ALD, CVD, PVD, or EB-IAD methods.
[0028]
[0047] In one embodiment, the processing chamber 100 includes a chamber body 102 and a showerhead 130 surrounding an interior region 106. The showerhead 130 may include a showerhead base and a showerhead gas distribution plate. Alternatively, the showerhead 130 may be replaced by a lid and nozzles in some embodiments, or by multiple pie-shaped showerhead compartments and plasma generation units in other embodiments. The chamber body 102 may be fabricated from aluminum, stainless steel, or other suitable materials, such as titanium (Ti). The chamber body 102 generally includes a sidewall 108 and a bottom 110. An outer liner 116 may be disposed adjacent to the sidewall 108 to protect the chamber body 102.
[0029]
[0048] An exhaust port 126 may be defined in the chamber body 102 and may couple the interior region 106 to a pumping system 128. The pumping system 128 may include one or more pumps and a throttle valve utilized to evacuate and regulate the pressure in the interior region 106 of the processing chamber 100.
[0030]
[0049] The showerhead 130 may be supported on a sidewall 108 of the chamber body 102. The showerhead 130 (or lid) may be opened to allow access to the interior region 106 of the processing chamber 100 and may provide a seal for the processing chamber 100 when closed. A gas panel 158 may be coupled to the processing chamber 100 to deliver process gases and / or cleaning gases to the interior region 106 through the showerhead 130 or the lid and nozzles. The showerhead 130 may be used in processing chambers used for dielectric etching (etching dielectric materials). The showerhead 130 may include a gas distribution plate (GDP) and may have multiple gas delivery holes 132 throughout the GDP. The showerhead 130 may include a GDP bonded to an aluminum base or an anodized aluminum base. The GDP may be made of Si or SiC, or may be made of YO, AlO, YAlO, or other suitable materials. 12 It may also be a ceramic such as (YAG).
[0031]
[0050] In processing chambers used for conductor etching (etching conductive materials), a lid may be used rather than a showerhead. The lid may include a central nozzle that fits into a central hole in the lid. The lid may be a ceramic, such as Al2O3, Y2O3, YAG, or a ceramic compound including a solid solution of Y4Al2O9 and Y2O3-ZrO2. The nozzle may be a ceramic compound, such as Y2O3, YAG, or a ceramic compound including a solid solution of Y4Al2O9 and Y2O3-ZrO2.
[0032]
[0051] Examples of process gases that can be used to process a substrate in the process chamber 100 include halogen-containing gases such as C2F6, SF6, SiCl4, HBr, NF3, CF4, CHF3, CH2F3, F, NF3, Cl2, CCl4, BCl3, and SiF4, among others, and other gases such as O2, or N2O. Examples of carrier gases include N2, He, Ar, and other gases that are inert to the process gas (e.g., non-reactive gases).
[0033]
[0052] The heater assembly 148 is disposed in the interior region 106 of the processing chamber 100 below the showerhead 130 or lid. The heater assembly 148 includes a support 150 that holds the substrate 144 during processing. The support 150 is attached to the end of a shaft 152 that is coupled to the chamber body 102 via a flange. The support 150, shaft 152, and flange may be composed of a heater material that includes AlN, for example, AlN ceramic. The support 150 may further include a mesa (e.g., a depression or a bump). The support may further include a wire, for example, a tungsten wire (not shown), embedded within the heater material of the support 150. In one embodiment, the support 150 may include metal heater and sensor layers sandwiched between AlN ceramic layers. Such an assembly may be sintered in a high temperature furnace to create a monolithic assembly. The layers may include heater circuits, sensor elements, ground planes, radio frequency grids, and combinations of metal and ceramic flow paths.
[0034]
[0053] A protective coating according to embodiments described herein may be deposited on at least a portion of any surface of the chamber components described herein (and those not shown in FIG. 1) that may be exposed to the process chemistries used in the process chamber. Exemplary chamber components that may be coated with the protective coatings described herein include, without limitation, electrostatic chucks, nozzles, gas distribution plates, showerheads (e.g., 130), electrostatic chuck components, chamber walls (e.g., 108), liners (e.g., 116), liner kits, gas lines, chamber lids, nozzles, shingle rings, process kit rings, edge rings, bases, shields, plasma screens, flow equalizers, cooling bases, chamber viewports, bellows, any portion of the heater assembly (including support 150, shaft 152, flanges), faceplates, blocker plates, and the like.
[0035]
[0054] 2A-2C show cross-sectional views of an article 210 having a protective coating deposited thereon according to various embodiments contemplated herein. The article 210 can be made of a ceramic (e.g., oxide-based ceramic, nitride-based ceramic, or carbide-based ceramic), a metal, or a metal alloy. Oxide-based ceramics include SiO2 (quartz), Al2O3, Y2O3, and the like. Examples of carbide-based ceramics include SiC, Si-SiC, and the like. Examples of nitride-based ceramics include AlN, SiN, and the like. In some embodiments, the article 210 can also be made of aluminum, anodized aluminum, aluminum alloys (e.g., Al 6061), or anodized aluminum alloys. In some embodiments, the article 210 can be made of stainless steel, nickel, nickel-chromium alloys, titanium, and the like. The terms "substrate," "article," and "chamber component" can be used interchangeably herein.
[0036]
[0055] As shown in FIGS. 2A to 2D, at least a portion of the surface of the article 210 is treated with M1 x F w , M1 x M2 y F w , and M1 x M2 y M3 z F w The metal fluoride may be coated with a protective coating (e.g., 220, 230, and 240) comprising at least one metal fluoride having a formula selected from the group consisting of: x F w In an embodiment, x is 1 and w ranges from 1 to 3. In an embodiment, the metal fluoride has the formula M1 x M2 y F w where x is in the range of 0.1 to 1, y is in the range of 0.1 to 1, and w is in the range of 1 to 3. In an embodiment, the metal fluoride is represented by the formula M1 x M2 y M3 z F wwhere x ranges from 0.1 to 1, y ranges from 0.1 to 1, z ranges from 0.1 to 1, and w ranges from 1 to 3. The values of x, y, z, and w may be integers or fractions. The ranges of x, y, z, and w include the end values (i.e., 0.1 and 1 for x, y, and z, and 1 and 3 for w). The ranges of x, y, z, and w include all single values within the specified ranges, and all subranges, integers, or fractions within the specified ranges. For example, x, y, and z may independently be, but are not limited to, about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, or about 1. Similarly, w may be about 1, about 2, or about 3, without being limited to integers only (as fractions are possible).
[0037]
[0056] In the metal fluoride formula, M1, M2, and M3 each represent a different metal. Exemplary metals suitable for M1, M2, and M3 include, but are not limited to, magnesium, yttrium, lanthanum, or aluminum. In certain embodiments, suitable metals for M1, M2, and M3 include magnesium, yttrium, and lanthanum. At least one of M1, M2, and M3 is either magnesium or lanthanum. Exemplary protective coatings as defined above include Mg x F w , La x F w , Y x Mg y F w , Y x La y F w , La x Mg y F w Or Y x Mg y La z F wThe protective coating composition may include at least one of the following: (a) a magnesium-containing metal fluoride or a lanthanum-containing metal fluoride; (b) a fluorine-containing chemical (such as a fluorine-containing plasma); and (c) a magnesium-containing metal fluoride. Although not intended to be limiting, magnesium-containing metal fluorides and lanthanum-containing metal fluorides are believed to be suitable protective coating candidates because the reaction product of the magnesium-containing or lanthanum-containing fluoride with a fluorine-containing chemical (such as a fluorine-containing plasma) is believed to have a lower vapor pressure than the reaction product of the substrate material with a fluorine-containing plasma (e.g., a reaction product of aluminum and fluorine). For example, the vapor pressure of AlF3 ranges from about 0.001 Torr to about 1000 Torr at temperatures of about 750°C to about 1250°C. In comparison, the vapor pressure of MgF2 ranges from about 0.001 Torr to about 0.1 Torr at temperatures of 1000°C to about 1250°C, and only reaches 1000 Torr at temperatures of about 2250°C. Similarly, LaF3 has a vapor pressure of about 10 Torr at temperatures of about 920°C to about 1120°C. -5 ~about 10 -3 , which is much lower than AlF3. For parts exposed to high temperatures above 650, the aluminum content in the protective coating can be minimized to reduce the formation of reaction products between aluminum and fluorides that can easily sublime. For parts that are unlikely to be exposed to temperatures above 650°C during processing, some aluminum can be introduced into the protective coating, but if introduced, it is preferably combined with at least one other metal (such as Mg and / or La).
[0038]
[0057] In other words, aluminum in an aluminum or aluminum alloy article exposed to a treatment gas (such as a fluorine-containing treatment gas or plasma) at a treatment temperature of, for example, 400°C to 1000°C will react with the fluorine in the treatment gas to produce AlF, which is highly volatile due to its high vapor pressure in the exemplary temperature range. xCoating an aluminum-based article with a protective coating containing the metal fluoride formulation described above is believed to reduce the number of particles generated for several reasons. Because the protective coating is already fluorinated, it is believed that fluorine from the processing environment is unlikely to attack the protective coating. Furthermore, the protective coating and its reaction products with fluorine from the processing environment (if any) may form seeds that are incompatible with the underlying article material and the fluorine (e.g., AlF x fluorine) in the processing environment, the products from such reactions are less likely to sublime and be deposited elsewhere in the chamber.
[0039]
[0058] Various coating structures are contemplated for the protective coating described herein. In one embodiment, the protective coating can be deposited directly onto the bare surface of the article. When the protective coating is deposited directly onto the bare surface of the article, the boundary between the bare surface of the article and the protective coating can be separate or not separate (e.g., the protective coating and the bare surface of the article can be intermixed / interdiffused / integral).
[0040]
[0059] In another embodiment, as shown in Figure 2A, the adhesion layer 205 may be deposited directly on the surface of the substrate, and the metal fluoride-containing protective coating 220 may be deposited on the adhesion layer. The adhesion layer 205 may be configured to improve the adhesive strength between the surface of the article 210 and the metal fluoride-containing protective coating 220. The adhesion layer 205 may also be configured to relieve stress by having a coefficient of thermal expansion (CTE) value, for example, between the CTE of the protective coating and the CTE of the article, to reduce potential CTE mismatch between the article and the protective coating. For example, the surface of the article (e.g., a processing chamber part) to be coated can be a metallic body (e.g., aluminum or an aluminum alloy such as Al 6061) or a ceramic body (e.g., Al2O3, AlN, SiC, etc.) having a CTE of about 22-25 ppm / K for aluminum and about 13 ppm / K for stainless steel, the adhesion layer can be amorphous Al2O3, and the metal fluoride coating can be MgO having a CTE closer to the CTE of the adhesion layer than the CTE of the article. x F w , La x F w , Y x Mg y F w , Y x La y F w , La x Mg y F w , or Y x Mg y La z F w In such embodiments, the buffer layer mitigates the difference in CTE between the protective coating and the processing chamber component, reducing susceptibility of the coating to cracking upon thermal cycling that may result from CTE mismatch.
[0041]
[0060] The adhesion layer 205 may also be configured as a diffusion barrier layer to prevent diffusion of fluorine-containing species (such as fluorine radicals) from the processing environment in a semiconductor processing chamber or from the fluorine-containing protective coating to the underlying article (e.g., through the grain boundaries of the protective coating). In certain embodiments, the adhesion layer 205 may be amorphous, such as amorphous alumina or amorphous yttrium aluminum garnet (YAG). The boundaries between the adhesion layer 205 and the underlying article 210 and / or between the adhesion layer 205 and the protective coating 220 deposited thereon may be separate or non-separate (e.g., the protective coating and the adhesion layer and / or the article and the adhesion layer may be intermixed / interdiffused / integral).
[0042]
[0061] The thickness of the adhesion layer described herein may range from about 5 nm to about 3000 nm, about 10 nm to about 1000 nm, about 15 nm to about 750 nm, about 20 nm to about 500 nm, about 25 nm to about 250 nm, about 30 nm to about 100 nm, about 50 nm, about 500 nm, or any subrange of thickness, or a single value thereof. The thickness and properties of the adhesion layer and any other layers of the protective coating described herein depend on the deposition method used to deposit said layers. These properties can be adjusted and tailored depending on the application of the coated article. For example, a protective coating deposited by ALD may have a thinner overall thickness and be deposited on a thin adhesion layer having a thickness of about 30 nm to about 100 nm. FIG. 9A shows an exemplary protective coating deposited by ALD on a thin adhesion layer, as described in more detail in the Examples. In comparison, protective coatings deposited by eye-gaze techniques such as PVD and EB-IAD have a greater overall thickness and can be deposited on a thicker adhesion layer having a thickness of about 250 nm to about 1000 nm. Figure 13 shows an exemplary protective coating deposited by EB-IAD on a thick adhesion layer, as described in more detail in the Examples.
[0043]
[0062] Another suitable coating structure of the fluorine-containing protective coating can be an uninterrupted continuous growth crystalline phase with a rough surface, as shown in FIG. 2B. The uninterrupted continuous growth crystalline phase type protective coating 230 can also be deposited on an adhesion layer (such as layer 205) or directly on the bare surface of the underlying article 210. In certain embodiments, the protective coating (e.g., 230) is designed with a certain roughness on the top surface of the coating so that if particles are generated during processing, the particles will mainly adhere to the coating of the semiconductor chamber parts and not to the wafer being processed. One method of roughening the top surface of the coating is to deblast the coating. Deblasting is commonly used, but is less preferred because particles generated during deblasting can shed at high processing temperatures and contaminate the wafer being processed in the processing chamber.
[0044]
[0063] In the present disclosure, the crystallinity of Mg-based metal fluorides and / or La-based metal fluorides is utilized to continuously grow crystalline Mg-based metal fluorides and / or crystalline La-based metal fluorides while controlling the nanoscale surface topography to achieve the target roughness. In other words, in the present disclosure, the nano- or micro-roughness of the top surface of the metal fluoride-containing protective coating can be tailored by controlling the deposition of the crystalline phase of the metal fluoride forming the protective coating 230. The resulting nano- or micro-roughness on the top surface of the metal fluoride-containing protective coating can be suitable for promoting the adhesion of particles generated during processing in the semiconductor processing chamber. In this way, if any particles are generated in the processing chamber during processing, such particles will adhere to the chamber parts instead of contaminating the wafer being processed. FIG. 9A, FIG. 9C1, FIG. 9C2, and FIG. 9C3 show a protective coating deposited by ALD having nano-roughness on the top surface of the protective coating, as described in more detail in the Examples.
[0045]
[0064] In certain embodiments, the roughness of the protective coating 230 is in the range of about 0.1 microinches to about 200 microinches, about 0.5 microinches to about 50 microinches, about 2 microinches to about 30 microinches, about 5 microinches to about 20 microinches, about 75 microinches to about 150 microinches, or about 30 microinches to about 100 microinches, or any subrange or single value therein.
[0046]
[0065] In certain embodiments, the microhardness of the protective coating 230 is greater than about 5 mN, greater than about 6 mN, greater than about 7 mN, greater than about 8 mN, greater than about 9 mN, greater than about 10 mN, greater than about 11 mN, or greater than about 12 mN. In certain embodiments, the microhardness of the protective coating 230 is at least twice as great as the microhardness of stainless steel and / or at least four times as great as the microhardness of alumina. The above microhardness values refer to the force applied to the protective coating to observe the first failure (or first crack formation) of the protective coating.
[0047]
[0066] Yet another suitable coating structure for the fluorine-containing protective coating is a multi-layer structure, such as a lamellar structure. The multi-layer structure may include, for example, multiple alternating layers of amorphous and crystalline layers (such as 240A, 240B, 240C, and 240D in FIG. 2C). In certain embodiments, the multi-layer protective coating can be formed on the adhesion layer 205, as described above with respect to FIGS. 2A and 2B. In other embodiments, the multi-layer protective coating can be deposited directly on the surface of the article 210.
[0048]
[0067] A multi-layer structure may include two layers of different composition. In some embodiments, a multi-layer structure may include three or more layers of different composition. A multi-layer structure may be deposited by a repeated super-cycle of any of the deposition techniques described herein. A super-cycle may mean that a first layer is deposited, followed by a second layer, followed by a subsequent layer, in some cases. Such a super-cycle may be repeated multiple times until a target thickness of the protective coating is achieved.
[0049]
[0068] In certain embodiments, the boundaries between the various layers of the multi-layer protective coating may be distinct, and / or the boundaries between the multi-layer protective coating and adhesive layer 205 (if present) may be distinct, and / or the boundaries between the multi-layer protective coating and adhesive layer 205 (if present) may be distinct, and / or the boundaries between adhesive layer 205 (if present) and the surface of article 210 may be distinct. In certain embodiments, one or more of these boundaries may or may not be distinct (i.e., adjacent layers may be intermixed / interdiffused / integral).
[0050]
[0069] In one exemplary embodiment, the multi-lamellar structure of the protective coating may include alternating layers of amorphous Al2O3 and crystalline MgF2. For example, 240A is an amorphous alumina layer, 240B is crystalline MgF2, 240C is amorphous alumina, 240D is crystalline MgF2, etc. Figures 10A1-10A3 and 11A1-11A3 show the structure of the MgF2 layer, as described in more detail in the Examples. x F w 1 shows an exemplary multi-layer protective coating of alternating layers of titanium and alumina.
[0051]
[0070] The protective coating can include any number of alternating layers, such as about 2 to about 250 layers, about 3 to about 200 layers, about 4 to about 150 layers, about 5 to about 100 layers, about 6 to about 50 layers, or about 7 to about 25 layers, or any subrange or single value therein. When the multi-layer protective coating is deposited by ALD, the number of alternating layers can be adjusted based on the number of ALD cycles performed to deposit each layer, as described in more detail below. The thickness of each layer can also be adjusted. For example, Mg x F w The protective coating comprising multiple alternating layers of Mg and alumina has a ratio of each Mg to alumina in the range of about 10:1 to about 10:1, about 8:1 to about 1:8, about 5:1 to about 1:5, about 3:1 to about 1:3, about 10:1 to about 1:1, about 8:1 to about 1:1, about 5:1 to about 1:1, or about 3:1 to about 1:1, or any subrange or single value therein. x F w The thickness of each alumina layer can have a ratio of 0.01 to 0.01 mm. An example of this is Mg x F w Although reference is made to alternating layers of alumina and aluminum oxide, this should not be construed as limiting, and similar thickness ratios would apply to other alternating layer configurations of the multi-layer protective coating.
[0052]
[0071] In certain embodiments, thin amorphous layers can be introduced between thicker crystalline layers in the protective coating to control the overall phase of the protective coating, e.g., tailoring the protective coating to be more amorphous.
[0053]
[0072] In certain embodiments, the structure and composition of the protective coating can be tailored to tailor the fluorine resistance of the protective coating and / or retard grain boundary attack by fluorine within the processing chamber.
[0054]
[0073] In certain embodiments, a multi-layer protective coating, such as that shown in FIG. 2C, or other protective coatings described herein (such as those shown in FIG. 2A and FIG. 2B), can be subjected to a post-coating treatment. Non-limiting exemplary post-coating treatments include annealing the protective coating, such as by subjecting the protective coating to a temperature in the range of about 400° C. to about 2500° C., about 450° C. to about 2000° C., or about 500° C. to about 1800° C., or any single value or subrange thereof, for a period of time of about 2 hours to about 24 hours, about 4 hours to about 15 hours, or about 6 hours to about 12 hours, or any single value or subrange therein. The annealing temperature and time can be selected based on the constituent materials of the article, surface, and protective coating to maintain their integrity and not deform, decompose, or melt any or all of these components. In certain embodiments, the protective coating can be post-treated to form a homogenous protective coating 240 having a uniform composition throughout the coating, as shown in FIG. 2D. Alternatively, post-treatment can be used to adjust the composition of the protective coating to create a compositional gradient within the coating.
[0055]
[0074] The composition of the various protective coatings can be tailored to achieve target coating properties based on the intended use of the coated article. For example, M1 x F wThe coating may include an M1 concentration of between about 5 atomic % and 100 atomic %, between about 10 atomic % and 95 atomic %, between about 20 atomic % and 90 atomic %, between about 20 atomic % and 80 atomic %, about 10 atomic %, about 20 atomic %, about 30 atomic %, about 40 atomic %, about 50 atomic %, about 60 atomic %, about 70 atomic %, about 80 atomic %, about 90 atomic %, or other ranges and / or values within these ranges, where the concentration is measured based on the total amount of metal in the metal fluoride protective coating. When the concentration is measured on the metal fluoride protective coating as a whole, the M1 concentration may be up to about 40 atomic %, up to about 35 atomic %, up to about 30 atomic %, up to about 25 atomic %, up to about 20 atomic %, up to about 15 atomic %, up to about 10 atomic %, up to about 5 atomic %, between about 20 atomic % and about 45 atomic %, or other ranges and / or values within these ranges.
[0056]
[0075] Metal fluoride protective coatings are of the formula M1 x M2 y F w %, M1 and 20-80 atomic % M2, 30-70 atomic % M1 and 30-70 atomic % M2, 40-60 atomic % M1 and 40-60 atomic % M2, 50-80 atomic % M1 and 20-50 atomic % M2, or 60-70 atomic % M1 and 30-40 atomic % M2, where the concentrations of M1 and M2 are measured based on the total amount of metal (M1+M2) in the metal fluoride protective coating. When measuring the concentration of the metal fluoride protective coating as a whole, the concentration of M1+M2 together can have a value of up to about 40 atomic %, up to about 35 atomic %, up to about 30 atomic %, up to about 25 atomic %, up to about 20 atomic %, up to about 15 atomic %, up to about 10 atomic %, up to about 5 atomic %, between about 20 atomic % and about 45 atomic %, or other ranges and / or values within these ranges.
[0057]
[0076] Metal fluoride protective coatings are of the formula M1 x M2 y M3 z F w%, M1 and 5-80 atomic % M2 and 5-80 atomic % M3; 10-70 atomic % M1 and 10-70 atomic % M2 and 10-70 atomic % M3; 1-90 atomic % M1 and 1-90 atomic % M2 and 1-90 atomic % M3, where the concentrations of M1, M2, and M3 are measured based on the total amount of metal (M1+M2+M3) in the metal fluoride protective coating. When measuring the concentration of the metal fluoride protective coating as a whole, the concentration of M1+M2+M3 together can have a value of up to about 40 atomic %, up to about 35 atomic %, up to about 30 atomic %, up to about 25 atomic %, up to about 20 atomic %, up to about 15 atomic %, up to about 10 atomic %, up to about 5 atomic %, between about 20 atomic % and about 45 atomic %, or other ranges and / or values within these ranges.
[0058]
[0077] The fluorine concentration in the metal fluoride protective coatings described herein can be from greater than 0 atomic % to about 95 atomic %, from about 5 atomic % to about 90 atomic %, from about 10 atomic % to about 85 atomic %, from about 20 atomic % to about 80 atomic %, from about 40 atomic % to about 75 atomic %, from about 50 atomic % to about 70 atomic %, or other ranges and / or values within these ranges.
[0059]
[0078] The resistance of a protective coating to plasma can be measured by the "etch rate" (ER), which has units of microns per hour (μm / hr) or angstroms per hour (Å / hr), during operation of the coated part and over the entire period of exposure to plasma (such as halogen or especially fluorine plasma). Measurements can be taken after different treatment times. For example, measurements can be taken before treatment, or at about 50 treatment times, or at about 150 treatment times, or at about 200 treatment times, etc. In one example, EB-IAD deposited MgF2 and ALD deposited MgF2 protective coatings according to embodiments were exposed to fluorine chemicals at a temperature of 650° C. for about 56 hours and showed no measurable coating loss. Changes in the composition of the protective coating deposited on the chamber parts can result in multiple different plasma resistance or erosion rate values. Furthermore, a protective coating comprising a single composition exposed to various plasmas can have multiple different plasma resistance or erosion rate values. For example, a plasma-resistant material may have a first plasma resistance or erosion rate associated with a first type of plasma and a second plasma resistance or erosion rate associated with a second type of plasma.
[0060]
[0079] 3 discloses a method 300 for reducing particles during processing in a semiconductor processing chamber, according to an embodiment. In the method 300, an article is provided (305) having at least a portion of one surface exposed to aggressive chemicals (e.g., halogen or fluorine based chemicals) typically found in processing chambers. At least a portion of the article that may be exposed to aggressive chemical reactions can be coated with a protective coating described herein. In certain embodiments, the surface to be coated is not roughened and the article is substantially free of microcracks.
[0061]
[0080] In certain embodiments, the method 300 further includes depositing an adhesion and fluorine diffusion barrier layer (310), such as the adhesion layer 205 described above. If an adhesion layer is present, the adhesion layer can be deposited by the same process as that for depositing the protective coating, or by a deposition process that is different from the deposition process for the protective coating. In certain embodiments, the adhesion layer can be deposited by one of atomic layer deposition (ALD), chemical vapor deposition (CVD), physical vapor deposition (PVD), or electron beam ion assisted deposition (EB-IAD).
[0062]
[0081] In certain embodiments, the method 300 further includes depositing a protective coating on the surface of the article to be coated (or on the adhesion layer, if present) by any one of atomic layer deposition (ALD), chemical vapor deposition (CVD), physical vapor deposition (PVD), or electron beam ion assisted deposition (EB-IAD) (315). The deposition method of the protective coating can be selected depending on the coating structure, target thickness, porosity, uniformity, conformality, composition, application, etc.
[0063]
[0082] In certain embodiments, the method 300 further includes subjecting the protective coating to a post-deposition treatment (320). One non-limiting example of such a post-deposition treatment includes annealing.
[0064]
[0083] The protective coating (and adhesion layer, if present) can be deposited by a variety of deposition techniques, but in certain embodiments, ALD is the preferred deposition technique. ALD may be advantageously used to deposit certain protective coatings described herein due to the high density, low porosity (0%), high uniformity, high conformality, ability to coat high aspect ratio surfaces and complex three-dimensional shapes, low defectivity, and high tenability associated with ALD techniques.
[0065]
[0084] Unlike ALD, methods such as thermal spraying, sputtering, plasma spraying, or evaporation techniques generally cannot deposit conformal, uniform coatings on complex topological features of a part with the low defect density of ALD coatings. Furthermore, ALD coatings can be deposited on non-roughened surfaces, in contrast to techniques such as plasma spraying, which involve pre-treatment by roughening the surface to be coated.
[0066]
[0085] Using ALD techniques, a crystalline metal fluoride-containing protective coating can be successively deposited in a controlled manner to promote particle adhesion, achieving target micro- or nano-roughness, as shown in FIG. 2B.
[0067]
[0086] Using ALD techniques, multilayer lamellar structures with alternating amorphous and crystalline layers can also be achieved, as shown in Figure 2C.
[0068]
[0087] Coatings deposited by ALD have a uniform thickness with less than ±20% thickness variation, or less than ±10% thickness variation, or less than ±5% thickness variation, or lower thickness variation when comparing the thickness of the coating at one location to the thickness of the coating at another location, or when quantifying the standard deviation of multiple thickness values obtained from a protective coating from multiple locations.
[0069]
[0088] ALD allows for the controlled, self-limiting deposition of materials by chemical reaction with the surface of an article. In addition to being a conformal and uniform process, in contrast to other deposition techniques, ALD is also capable of forming very thin films.
[0070]
[0089] 4A illustrates an example of an ALD process 400 that can be utilized to deposit a protective coating as described herein. In process 400, an adhesion layer 205 is deposited on a surface of an article 210. The article (optionally having an adhesion layer thereon) is then coated with a protective coating. The cycle illustrated in process 400 begins with one or more precursors 490A and 490B flooding into an ALD chamber and adsorbing onto the surface of the substrate (including the surface of the pore walls within the substrate). In the illustrated process 400, precursors 490A and 490B are adsorbed onto the surface of adhesion layer 205. In the present disclosure, precursors 490A and 490B can be one or more metal precursors of M1, M2, M3, or combinations thereof.
[0071]
[0090] Metal fluorides have the formula M1 x F w When the metal fluoride is of the formula M1, a single metal precursor 490A of the metal M1 may be introduced into the ALD chamber, or two or more metal precursors of the metal M1 may be introduced into the ALD chamber. x M2 y F w In the case of metal fluoride, a single metal precursor 490A of metal M1 and a single metal precursor 490B of metal M2 can be introduced to the ALD chamber, or two or more metal precursors of each of metal M1 and / or metal M2 can be introduced to the ALD chamber. x M2 y M3 z F w In this case, a single metal precursor 490A of metal M1, a single metal precursor 490B of metal M2, and a single metal precursor of metal M3 (not shown) can be introduced to the ALD chamber, or two or more metal precursors of each of metal M1 and / or metal M2 and / or metal M3 can be introduced to the ALD chamber.
[0072]
[0091] When two or more metal precursors are introduced into the ALD chamber, they may be introduced simultaneously (e.g., co-dosed) or sequentially (co-deposition). Whether co-dosed or co-deposited, the one or more metal precursors form an adsorbed layer 440A (also referred to as a first half reaction). Excess precursors are then flushed from the ALD chamber before one or more reactants 492 are introduced into the ALD chamber and subsequently flushed away. In the present disclosure, the reactant may be a fluorine-containing reactant in one embodiment, or an oxygen-containing reactant in another embodiment that is subsequently subjected to fluorination (e.g., in situ fluorination). When reactant 492 is a fluorine-containing reactant, it reacts with the adsorbed layer 440A to form a fluorine-containing reactant having the formula M1 x F w、 M1 x M2 y F w , or M1 x M2 y M3 z F w When reactant 492 is an oxygen-containing reactant, it reacts with adsorbed layer 440A to form a first layer 230A having the formula M1 x O a、 M1 x M2 y O a , or M1 x M2 y M3 z O a forming a first layer having the formula M1 x F w、 M1 x M2 y F w , or M1 x M2 y M3 z F w The reactants may be fluorinated after or during the ALD cycle (e.g., in-situ fluorination) to form a first layer 230A having the metal precursors. As with the metal precursors, when multiple reactants are introduced during ALD, they may be introduced simultaneously (e.g., co-dosed) or sequentially (co-deposition).
[0073]
[0092] "Co-deposition" refers to atomic layer deposition in which metal precursors or oxygen-containing reactants or fluorine-containing reactants are co-injected sequentially (i.e., one metal precursor is injected followed by another metal precursor, and only after a mixture of different metal precursors is deposited is a reactant introduced to react with the precursors). The concentrations of the various components in the co-deposition can be related to the injection rates of each component.
[0074]
[0093] "Co-dosing" refers to atomic layer deposition in which metal precursors or O-containing reactants or F-containing reactants are simultaneously co-injected (i.e., one metal precursor is simultaneously dosed with a second metal precursor, and only after a mixture of different metal precursors is deposited is a reactant introduced to react with the precursors). The concentrations of the various components in the co-dosing can be related to the injection rate of each component.
[0075]
[0094] Flooding the ALD chamber with one or more metal precursors of M1, M2, M3, or combinations thereof, purging the ALD chamber from excess metal precursors, flooding the ALD chamber with one or more fluorine-containing or oxygen-containing reactants, and purging the ALD chamber from excess reactants can be referred to as a supercycle of process 400. Such a supercycle can be repeated n times to form a protective coating 230 (e.g., an uninterrupted continuous protective coating), such as having, but not limited to, a target micro- or nano-roughness. n is an integer and can represent a finite number of ALD supercycles selected based on a target thickness of the protective coating.
[0076]
[0095] 4B illustrates another example of an ALD process 410, which may be referred to herein as a continuous ALD deposition. This process may be utilized to form a multi-layer lamellar protective coating (such as that shown in FIG. 2C) by including a supercycle in which: a first layer 240A may be deposited as described above with respect to process 400 until a first target thickness of the first layer 240A is reached, then a second layer 240B (compositionally different from the first layer 240A) may be deposited as described above with respect to process 400 until a second target thickness of the second layer 240B is reached, followed by a similar deposition of an additional compositionally different layer. This supercycle may be repeated w times to achieve a multi-layer lamellar protective coating of the target thickness as shown in FIG. 2C.
[0077]
[0096] In process 410, first layer 240A is formed by flooding one or more precursors (480) of metals M1, M2, M3, or combinations thereof into an ALD deposition chamber to react with (optional) adhesion layer 205 and deposit first adsorbed layer 422. The ALD deposition chamber is then purged to flush out excess precursor 480. One or more fluorine-containing or oxygen-containing reactants 482 are then introduced into the ALD chamber to react with first adsorbed layer 422 and ultimately deposit M1. x F w ,M1 x M2 y F w and M1 x M2 y M3 z F w The cycle of forming the first layer 240A may be repeated m times until a first target thickness of the first layer 240A is achieved, where m is an integer and may represent a finite number of ALD cycles selected based on the first target thickness of the first layer in the protective coating.
[0078]
[0097] The first target thickness may be in the range of about 1 nm to about 3000 nm, about 5 nm to about 2000 nm, about 10 nm to about 1000 nm, about 15 nm to about 750 nm, about 20 nm to about 500 nm, about 25 nm to about 400 nm, about 35 nm to about 300 nm, or about 50 nm to about 250 nm, or any subrange or single value therein.
[0079]
[0098] In process 410, second layer 240B is formed by flooding one or more precursors (484) of metals M1, M2, M3, or combinations thereof into the ALD deposition chamber to react with first layer 240A and deposit second adsorbed layer 426. The ALD deposition chamber is then purged to flush out excess precursor 484. One or more fluorine-containing or oxygen-containing reactants 486 are then introduced into the ALD chamber to react with second adsorbed layer 426 and ultimately deposit M1. x F w , M1 x M2 y F w and M1 x M2 y M3 z F w The cycle of forming a second layer 240B, compositionally distinct from the first layer 240A, may be repeated p times until a second target thickness of the second layer 240B is achieved, where p is an integer and may represent a finite number of ALD cycles selected based on the second target thickness of the second layer in the protective coating.
[0080]
[0099] The second target thickness may be in the range of about 1 nm to about 3000 nm, about 5 nm to about 2000 nm, about 10 nm to about 1000 nm, about 15 nm to about 750 nm, about 20 nm to about 500 nm, about 25 nm to about 400 nm, about 35 nm to about 300 nm, or about 50 nm to about 250 nm, or any subrange or single value therein.
[0081]
[0100] In the case of ALD, the final thickness of the material depends on the number of reaction cycles performed, since each reaction cycle grows a layer of a particular thickness, which may be an atomic layer or a fraction of an atomic layer. These supercycles may be repeated k times until a multi-lamellar protective coating of the target number of layers (e.g., 240A, 240B, 240C, 240D, etc.) and target thickness is achieved. k represents a finite number of ALD supercycles selected based on the target thickness of the overall protective coating and the number of alternating first and second layers of the multi-lamellar protective coating. A multi-lamellar protective coating may also be referred to as a "stack of multiple layers" or a "nanolaminate coating" or similar variations thereof.
[0082]
[0101] The total thickness of the protective coating deposited by ALD can be from about 5 nm to about 3 μm, from about 10 nm to about 2 μm, from about 20 nm to about 1 μm, from about 30 nm to about 750 nm, from about 40 nm to about 500 nm, or from about 50 nm to about 250 nm, or any single value or subrange therein.
[0083]
[0102] ALD techniques can deposit thin layers of material at relatively low temperatures (e.g., about 25°C to about 350°C) so as not to damage or deform the materials of the chamber components. The optimal temperature range for a particular ALD process is called the "ALD temperature window." At temperatures below the ALD temperature window, growth rates may decrease and non-ALD type deposition may occur. At temperatures above the ALD temperature window, reactions may occur in a chemical vapor deposition (CVD) mechanism. The ALD temperature window may range from about 25°C to about 350°C. In some embodiments, the ALD temperature window is from about 25°C to about 200°C, or from about 25°C to about 1510°C, or from about 100°C to about 120°C, or from about 25°C to about 125°C, or from about 25°C to about 350°C.
[0084]
[0103] Additionally, ALD techniques can also deposit layers of material within complex features (e.g., high aspect ratio features) of a part. In certain embodiments, a surface coated with a protective coating described herein has at least a portion with a high aspect ratio (e.g., a depth:width (D:W) ranging from about 2:1, about 5:1, or about 10:1 to about 50:1, about 100:1, about 200:1, or about 300:1), and according to embodiments, the high aspect ratio portion is conformally and uniformly coated with the protective coating. The term "uniform" refers to a protective coating having a thickness variation of less than about + / - 20%, a thickness variation of less than about + / - 10%, a thickness variation of less than about + / - 5%, or lower thickness variation when comparing the average thickness of the coating or the standard deviation of the thickness of the coating from one location to another.
[0085]
[0104] Furthermore, ALD techniques generally produce coatings that are very dense, relatively thin (i.e., 1 μm or less) with low porosity, such as less than about 1.5%, less than about 1%, less than about 0.5%, or no porosity (i.e., no pinholes), and can eliminate the formation of cracks during deposition. As used herein, the term "porosity-free" means the absence of any pores, pinholes, or voids along the entire depth of the coating as measured by transmission electron microscopy (TEM).
[0086]
[0105] As discussed with respect to ALD techniques, in certain embodiments, the metal fluoride comprising the protective coating is a metal oxide species (e.g., M x M2 y M3 z O a) (among other steps). Thus, in certain embodiments, the protective coating can contain some amount of oxygen atoms, such as up to 40 atomic % oxygen. In certain embodiments, the amount of oxygen can be reduced to single digit atomic % (e.g., less than 10 atomic %) or eliminated entirely (e.g., 0 atomic % oxygen). In certain embodiments, the amount of oxygen in the protective coating can range anywhere from 0 atomic %, about 2 atomic %, about 4 atomic %, about 6 atomic %, about 8 atomic %, about 10 atomic %, or anywhere from about 15 atomic % to about 20 atomic %, about 25 atomic %, about 30 atomic %, about 35 atomic %, or about 40 atomic %. Similar oxygen concentrations can be achieved in protective coatings deposited by other techniques (e.g., CVD, EB-IAD, and PVD) and are not limited to protective coatings deposited exclusively by ALD.
[0087]
[0106] The atomic percentages of the various components (i.e., M1, M2, M3, F, and optionally O) of the metal fluoride protective coating can be adjusted based on the intended application and intended properties of the protective coating. For example, the composition can be adjusted to control and / or achieve a target vapor pressure of the coating. Thus, in certain embodiments, the disclosure is directed to a method for adjusting / controlling the vapor pressure of the protective coating. In another example, the composition can be adjusted to modify / adjust / enhance the fluorine resistance of the protective coating. Thus, in certain embodiments, the disclosure is directed to a method for modifying / adjusting / enhancing the fluorine resistance of the protective coating. In yet another example, the composition of the coating can be adjusted to control the phase (e.g., amorphous or crystalline) and structure of the protective coating. Thus, in certain embodiments, the disclosure is directed to a method for controlling the phase and / or structure of the protective coating.
[0088]
[0107] With ALD, the composition and properties of the protective coating, such as vapor pressure, fluorine resistance, and structure, can be tuned by the choice of metal precursor, reactant, and number of cycles (n, m, k, p).
[0089]
[0108] The precursors that can be used with the ALD processes described herein depend on the particular metal fluoride layer being formed.
[0090]
[0109] For example, suitable Mg precursors include, without limitation, the following ligand categories: Cp (cyclopentadienyl), thd (tetraheptanedionate), and amd (amidinate) with various sub-R-groups (Et, Me, Bu, Pr, etc.).
[0091]
[0110] For example, suitable La precursors include, without limitation, lanthanum silylamides, La[N(SiMe3)2]3, and heteroleptic precursors such as the following ligand categories: thd, Cp compounds, amidinates, and Cp-amd.
[0092]
[0111] For example, suitable Y precursors include, without limitation, tris(N,N-bis(trimethylsilyl)amido)yttrium(III), tris(2,2,6,6-tetramethyl-3,5-heptanedionato)yttrium(III) or yttrium(III) butoxide, yttrium cyclopentadienyl compounds (e.g., tris(cyclopentadienyl)yttrium (CpY), tris(methylcyclopentadienyl)yttrium ((CpMe)Y), tris(butylcyclopentadienyl)yttrium, tris(cyclopentadienyl)yttrium, tris(ethylcyclopentadienyl)yttrium), or combinations thereof. Other yttrium-containing precursors that can be used include yttrium-containing amide-based compounds (e.g., tris(N,N'-di-i-propylformamidinato)yttrium or tris(bis(trimethylsilyl)amido)lanthanum) and yttrium-containing beta-diketonate-based compounds.
[0093]
[0112] For example, suitable Al precursors include, without limitation, diethylaluminum ethoxide, tris(ethylmethylamido)aluminum, aluminum sec-butoxide, aluminum tribromide, aluminum trichloride, triethylaluminum, triisobutylaluminum, trimethylaluminum, tris(diethylamido)aluminum, or combinations thereof.
[0094]
[0113] The oxygen reactant used by an ALD system to form a metal oxide layer (before the layer is fluorinated to form a metal fluoride as described herein) can be oxygen, water vapor, ozone, oxygen, oxygen radicals, an alcohol, another oxygen source, or a combination thereof.
[0095]
[0114] The fluoride reactant used by an ALD system to form a metal fluoride layer can be, for example, a fluoride (e.g., TiF4, HF, Hhfac, tetrafluoropropanol, hexafluoropropanol, hexafluoro-acetylacetone, NF3, HF-pyridine), another fluorine source, or a combination thereof.
[0096]
[0115] Referring again to FIG. 4B, in certain embodiments, the multi-layer protective coating deposited by ALD can be subjected to a post-deposition treatment, such as annealing, to form, for example, a homogenous protective coating 240.
[0097]
[0116] Another deposition technique that can be utilized to deposit the protective coatings described herein is chemical vapor deposition (CVD). Figure 5 illustrates an exemplary chemical vapor deposition (CVD) system that can be utilized to coat an article, according to one embodiment.
[0098]
[0117] The system includes a chemical vapor precursor delivery system 505 and a CVD reactor 510. The role of the vapor precursor delivery system 505 is to generate a vapor precursor 520 (such as a vapor precursor of metals M1, M2, M3, or a combination thereof) from a starting material 515, which can be in solid, liquid, or gas form. The vapor is then transported to the CVD reactor 510 and deposited as a thin film 545 (e.g., M1) on an article 530 (e.g., a semiconductor process chamber part) that is placed on an article holder 535. x F w , M1 x M2 y F w and M1 x M2 y M3 z F w The metal fluoride is deposited as a metal fluoride having a formula selected from the group consisting of:
[0099]
[0118] The CVD reactor 510 heats the article 530 to a deposition temperature using a heater 540. In some embodiments, the heater may heat the walls of the CVD reactor (also called a "hot-wall reactor"), which can transfer heat to the article. In other embodiments, the walls of the CVD reactor may be kept cool, while only the molded article is heated (also called a "cold-wall reactor"). It should be understood that the configuration of the CVD system should not be construed as limiting. A variety of equipment is available for CVD systems, and the equipment is selected to provide optimal processing conditions that result in a coating of uniform thickness, surface morphology, structure, and composition.
[0100]
[0119] Various CVD processes consist of the following process steps: (1) generating activated gaseous reactive species (also known as "precursors") from starting materials; (2) transporting the precursors to a reaction chamber (also called a "reactor"); (3) absorbing the precursors onto a heated article; (4) engaging in a chemical reaction between the precursors and the article at the gas-solid interface to form deposits and gaseous by-products; and (5) removing the gaseous by-products and unreacted gaseous precursors from the reaction chamber.
[0101]
[0120] Suitable CVD precursors may be stable at room temperature, may have a low evaporation temperature, may generate stable vapors at low temperatures, have a suitable deposition rate (low deposition rate for thin coatings and high deposition rate for thick coatings), and relatively low toxicity, may be cost-effective, and may be relatively pure. For some CVD reactions, such as pyrolysis reactions (also known as "pyrolysis") or disproportionation reactions, the chemical precursor alone may be sufficient to complete the deposition. For other CVD reactions, in addition to the chemical precursor, other reagents or reactants (such as oxygen- or fluorine-containing reactants) may be utilized to complete the deposition to form a metal fluoride protective coating, such as those described herein.
[0102]
[0121] CVD has many advantages, including the ability to deposit dense, pure coatings and produce uniform films with good reproducibility and adhesion at reasonably high deposition rates. In embodiments, layers deposited using CVD may have less than 1% porosity and less than 0.1% (e.g., about 0%) porosity. Thus, it can be used to uniformly coat parts with complex geometries and deposit conformal films with good conformal coverage (e.g., substantially uniform thickness). CVD may also be utilized to deposit multi-component films, for example, by feeding multiple chemical precursors (e.g., two or more of M1, M2, M3) in predetermined ratios to a mixing chamber and feeding the mixture to a CVD reaction system. In certain embodiments, CVD deposition rates are higher than ALD, but still provide many of the above-mentioned advantages associated with ALD deposition. Additionally, the high deposition rates of CVD can lead to higher throughput and lower costs of protective coatings. Thus, in certain embodiments, CVD may be the deposition technique of choice, at least in part, due to its high deposition rates, high throughput, and low cost.
[0103]
[0122] In certain embodiments, a CVD system such as that depicted in FIG. 5 or a similar system is utilized to deposit any of the protective coatings described herein by CVD. In certain embodiments, the protective coating is a Mg x F w , La x F w , Y x Mg y F w , Y x La y F w , La x Mg y F w , or Y x Mg y La z F w In certain embodiments, the protective coating can have any of the coating structures described above (e.g., multi-layer structures, continuous uninterrupted coatings, and coatings deposited on an adhesion layer 525 disposed between the coating 545 and the surface of the article 530).
[0104]
[0123] For thicker protective coatings (e.g., on the micrometer scale), techniques such as EB-IAD and PVD can be beneficially employed to deposit the protective coatings described herein. These techniques, like ALD, can be used to deposit protective coatings over adhesion layers, continuous single protective layers, and multi-layer protective coatings.
[0105]
[0124] FIG. 6 depicts an exemplary physical vapor deposition (PVD) system that may be utilized to coat an article, according to an embodiment. Various PVD processes have three basic steps in common: (1) evaporation of material from a solid source with the aid of a high temperature or gaseous plasma; (2) transport of the vaporized material in a vacuum to the surface of the article; and (3) condensation of the vaporized material onto the article to produce a thin film layer. An exemplary PVD reactor is shown in FIG. 6 and will be discussed in more detail below.
[0106]
[0125] In FIG. 6, a PVD reactor chamber 600 includes a plate 610 adjacent to an article 620 and a plate 615 adjacent to a target 630. Air may be removed from the reactor chamber 600 to form a vacuum. Argon gas may then be introduced into the reaction chamber and a voltage may be applied to the plates (610, 615) to generate a plasma consisting of electrons and positive argon ions 640. The positive argon ions 640 may be attracted to the negative plate 615 where they may collide with the target 630, ejecting atoms 635 from the target. The ejected atoms 635 may be transported and deposited as a protective coating 645 on an optional adhesion layer 625 that is deposited on the surface of the article 620.
[0107]
[0126] A PVD reactor such as that shown in FIG. 6, or a PVD reactor of similar operating principles, can be utilized to deposit any of the protective coatings described herein by PVD. In certain embodiments, the protective coating deposited by PVD is a Mg x F w , La x F w , Y x Mg y F w , Y x La y F w , La x Mg y F w , or Y x Mg y La z F w The metal fluoride coating may include at least one of 。 In certain embodiments, the protective coating deposited by PVD can have any of the coating structures described above (such as a multi-layer structure, a continuous uninterrupted coating, and a coating deposited on an adhesion layer 625 disposed between the coating 645 and the surface of the article 630).
[0108]
[0127] Suitable targets that may be used to deposit the metal fluoride protective coatings described herein include Mg metal, La metal, Y, Al, sintered fluoride bodies or metal targets via a reactive F source.
[0109]
[0128] In certain embodiments, PVD techniques provide relatively higher deposition rates than certain other deposition techniques, such as ALD. In certain embodiments, PVD also provides additional process knobs for controlling the stress state of the coating, which can be an additional advantage. For example, increased hardness of the coating can be achieved through the high compressive stress state of the coating, which can help improve the sputtering resistance of the coating deposited by PVD compared to coatings deposited by certain other techniques.
[0110]
[0129] In certain embodiments, EB-IAD can be an advantageous alternative to deposition techniques such as plasma spraying. Plasma spraying techniques rely on deblasting to increase the surface roughness of the underlying substrate to promote adhesion of the coating onto the substrate's surface. The deblasting used to roughen the underlying substrate causes the underlying substrate to become filled with microcracks. In contrast, deblasting is not part of the EB-IAD deposition process. Thus, EB-IAD coated substrates are not roughened and do not have as many microcracks as plasma spray coated substrates.
[0111]
[0130] 7A illustrates a deposition mechanism applicable to various deposition techniques utilizing energetic particles, such as ion-assisted deposition (IAD). Exemplary IAD methods include deposition processes for forming plasma-resistant protective coatings described herein that incorporate ion bombardment such as evaporation (e.g., activated reactive evaporation (ARE)) and sputtering under ion bombardment.
[0112]
[0131] One particular type of IAD performed in embodiments is e-beam IAD. Any of the IAD methods can be performed in the presence of reactive gas species, such as O2, N2, halogens (e.g., fluorine), argon, etc. The reactive species can burn off organic contaminants on the surface prior to and / or during deposition. In certain embodiments, the IAD deposition is performed in the presence of fluorine to deposit a metal fluoride protective coating.
[0113]
[0132] As shown in Figure 7A, a protective coating 715 (similar to the protective coatings in the previous figures) is formed on an article 710 (such as a chamber component) or on an adhesion layer disposed between a surface of the article 710 and the protective coating 715. In Figures 7A and 7B, the protective coating 715 is formed by the accumulation of a deposition material 702 in the presence of energetic particles 703, such as ions. The deposition material 702 can include atoms, ions, radicals, etc. The energetic particles 702 can impact and compress the protective coating 715 as it is formed.
[0114]
[0133] In one embodiment, EB-IAD is utilized to form the plasma resistant protective coating 715. FIG. 7B is a schematic diagram of an IAD deposition apparatus. As shown, a material source 750 provides a flux of deposition material 702, and an energetic particle source 755 provides a flux of energetic particles 703, both of which bombard the article 710 through the IAD process. It should be noted that the energetic particle source 755 may be an ion source, such as oxygen or fluorine. The energetic particle source 755 may also provide other types of energetic particles, such as radicals, neutrons, atoms, and nano-sized particles, from a particle generation source (e.g., from a plasma, reactive gas, or from a material source providing the deposition material).
[0115]
[0134] The material source (e.g., target body or plug material) 752 used to provide the deposition material 702 may be a metal corresponding to the same metal of which the protective metal fluoride coating 715 is to be constructed. The material source may be or include Mg or other materials used to form the protective coating. The material source may be in the form of sintered bodies, pellets, granules, or powders. In some embodiments, multiple material sources are used, such as a first material source of Mg target and a second material source of bulk sintered Al2O3 target. Other target materials such as powders, calcined powders, preformed materials (e.g., formed by green pressing or hot pressing), or machined bodies (e.g., molten materials) may also be used. All of the different types of material sources 750 are dissolved in the molten material source during deposition. However, different types of starting materials require different times to melt. Thus, the EB-IAD deposition may be optimized to deposit a metal fluoride protective coating with target composition and properties.
[0116]
[0135] The IAD may utilize one or more plasmas or beams (e.g., electron beams) to provide a source of material and energetic ions. It may also provide reactive species during deposition of the plasma resistant coating. In one embodiment, the energetic particles 703 include at least one of non-reactive species (e.g., Ar) or reactive species (e.g., O). In further embodiments, reactive species such as CO and halogens (Cl, F, Br, etc., especially F) may also be introduced during the formation of the protective coating.
[0117]
[0136] In an IAD process, the energetic particles 703 can be controlled by an energetic ion (or other particle) source 755, independent of other deposition parameters. According to the energy (e.g., velocity), density and incidence angle of the energetic ion flux, the composition, structure, crystal orientation, grain size and amorphous or crystalline nature of the protective coating can be manipulated. In certain embodiments, the deposition rate ranges from about 0.1 Å / s to about 2 Å / s, from about 0.1 Å / s to about 2 Å / s, or from about 0.5 Å / s to about 1 Å / s. Without being limited thereto, it is believed that a higher deposition rate and / or higher ion assist (also referred to herein as "high IAD") contributes to a protective coating layer that is more uniform, denser and has a more compact structure.
[0118]
[0137] Additional parameters that can be adjusted are the temperature of the article during deposition and the duration of deposition. In one embodiment, the IAD chamber includes heat lamps to provide heating. In another embodiment, the IAD chamber and the article being coated are not heated. If the chamber is not heated, the temperature naturally increases as a result of the IAD process. Higher temperatures during deposition can increase the density of the protective coating, but can also increase the mechanical stress of the protective coating. Active cooling can be added to the chamber to maintain a low temperature during coating. In certain embodiments, the metal fluoride protective coatings described herein are deposited by EB-IAD at temperatures ranging from about 50° C. to about 400° C., or from about 150° C. to about 300° C.
[0119]
[0138] Additional parameters that can be adjusted for EB-IAD are the working distance and the incidence angle. The working distance is the distance between the material source 752 and the article 710. Reducing the working distance can increase the deposition rate and improve the effectiveness of the ion energy. However, reducing the working distance below a certain point can compromise the uniformity of the protective layer. The incidence angle is the angle at which the deposition material 702 hits the article 710.
[0120]
[0139] IAD coatings can be applied to a wide range of surface conditions, with roughness ranging from about 0.1 microinches (μin) to about 180 μin. However, a smoother surface will facilitate uniform application. Additionally, EB-IAD can be used without pre-treatment of the surface to be coated, and therefore can be used on unroughened surfaces.
[0121]
[0140] In certain embodiments, the EB-IAD coatings can be amorphous. Amorphous coatings are more conformal and reduce epitaxial cracking caused by lattice mismatch compared to crystalline coatings. In other embodiments, the EB-IAD protective coatings described herein are crystalline.
[0122]
[0141] Co-deposition of multiple targets using multiple electron beam (e-beam) guns can be achieved to create thicker coatings and layered structures. For example, two targets of the same material can be used simultaneously. Each target can be irradiated with a different e-beam gun. This increases the deposition rate and thickness of the protective layer. In another example, the two targets can be different ceramic materials. For example, one target of Mg and another target of Y can be used. A first e-beam gun can bombard the first target to deposit a first protective layer, followed by a second e-beam gun bombarding the second target to form a second protective layer having a different material composition than the first protective layer.
[0123]
[0142] In one embodiment, a single target material (also referred to as a plug material) and a single electron beam gun can be used to arrive at the plasma resistant protective coatings described herein.
[0124]
[0143] In one embodiment, multiple chamber parts are processed in parallel in the IAD chamber. Each chamber part can be supported by a different fixture. Alternatively, one fixture can be configured to support multiple chamber parts. The fixture can move the supported chamber parts during deposition.
[0125]
[0144] In one embodiment, the fixture supporting the chamber parts can be designed from metal components such as cold rolled steel or ceramics such as Al2O3, Y2O3. The fixture can be used to support the chamber parts above or below the material source and the electron beam gun. The fixture can have a chucking function to chuck the chamber parts for safer and easier handling as well as during coating. The fixture can also have the ability to orient or align the chamber parts. In one embodiment, the fixture can be repositioned and / or rotated about one or more axes to change the orientation of the supported chamber parts relative to the source material. The fixture may also be repositioned to change the working distance and / or incidence angle before and / or during deposition. The fixture can have cooling or heating channels to control the temperature of the chamber parts during coating. Since IAD is an eye-gaze process, the ability to reposition and rotate the chamber parts may enable maximum coating coverage of 3D surfaces such as holes.
[0126]
[0145] Metal fluoride protective coatings deposited by EB-IAD can be thicker than those deposited by ALD or CVD. For example, such coatings can have a thickness in the range of about 50 nm to about 10 μm, about 100 nm to about 8 μm, about 250 nm to about 5 μm, about 500 nm to about 3 μm, or about 750 nm to about 2 μm, or any subrange or single value therein.
[0127]
[0146] The microstructure and / or porosity of protective coatings deposited by EB-IAD depends on the topography of the underlying substrate, in certain embodiments, the porosity of metal fluoride protective coatings deposited by EB-IAD ranges from 0% to 35%, up to 30%, up to 25%, up to 20%, up to 15%, up to 10%, up to 5%, or up to 1%, or any subrange or single value therein.
[0128] Illustrative Examples
[0147] The following examples are provided to aid in the understanding of the present disclosure and should not be construed as specifically limiting the disclosure described and claimed herein. Such variations of the present disclosure, including the substitution of all equivalents, now known or later developed, that are within the scope of those skilled in the art and may be minor changes in formulation or experimental design, should be considered to be within the scope of the disclosure incorporated herein.
[0129] Example 1-M1 x F w Atomic Layer Deposition (ALD) of Protective Coatings
[0148] Illustrative here is the formula M1 x F w The protective coating was deposited by ALD, for example, using the process shown in FIG. 4A or 4B. In this example, a magnesium precursor was utilized in combination with an oxygen reactant to form a compound of formula M1 x O a The protective coating was then fluorinated (e.g., by exposure to a fluorine species) to form a protective coating of M1 x F w The protective coating in this example was deposited directly onto the surface of the article (in this example, onto the native oxide on the surface of the article) and was not a separately deposited adhesion layer.
[0130]
[0149] 8A shows a cross-sectional view of an article coated with the protective coating deposited by ALD as described above according to one embodiment as viewed on a 100 nm scale by scanning electron microscope (SEM). From the SEM image, the thickness of the protective coating was observed to be about 290 nm. Furthermore, the protective coating was confirmed to be crystalline.
[0131]
[0150] Figure 8B shows an energy dispersive X-ray spectroscopy (EDS) line scan of the protective coating observed in Figure 8A. From section A of Figure 8B, it was observed that the coating contained oxygen at a concentration of about 35 atomic % (line 810). Therefore, the protective coating is also referred to as Mg-OF. The fluorine concentration in the protective coating was about 25 atomic % (line 820), and the magnesium concentration in the protective coating was about 30 atomic % (line 830).
[0132] Example 2 - Continuous, uninterrupted protective coating deposited by ALD
[0151] Illustrative here is the formula M1 x F w The protective coating was deposited successively by ALD, for example, using the process shown in FIG. 4A or FIG. 4B. In this example, x F w A magnesium precursor was utilized in combination with a fluorine reactant to form a protective coating of MgO, where M1 is Mg. The protective coating was deposited in a continuous manner to form a crystalline MgO coating having a uniform composition and thickness throughout the coating except at the surface of the coating. x F w The nano-roughness is created to improve adhesion of the protective coating to any particles that may be formed during processing so that such particles do not contaminate the processed wafer. The protective coating in this example was deposited on an adhesion layer disposed on the surface of the article.
[0133]
[0152] FIG. 9A illustrates a 200 nm-scale transmission electron microscope (SEM) view of an amorphous alumina adhesion layer 920 (corresponding to section B of FIG. 9B) and Mg x F w 9B)。 Shown is a cross-sectional view of an AlN article 910 (corresponding to section C of FIG. 9B) coated with a protective coating 930 (corresponding to section C of FIG. 9B).
[0134]
[0153] FIG. 9B shows an EDS line scan of the protective coating observed in FIG. 9A. From section A of FIG. 9B, Mg x F w The protective coating was observed to contain a low oxygen content of less than 5 atomic % (line 940). The fluorine concentration in the protective coating (section A) was about 70 atomic % (line 950), and the magnesium concentration in the protective coating (section A) was about 25 atomic % (line 960).
[0135]
[0154] From section B of Figure 9B, it was observed that the amorphous alumina adhesion layer contained oxygen at a concentration of about 70 atomic % and aluminum at a concentration of about 25 atomic %. The boundary between the protective coating 930 and the adhesion layer 920 appeared to be discrete rather than intentionally diffuse.
[0136]
[0155] From section C of Figure 9C, it was observed that the coated article was made of AlN with N at a concentration of about 65 atomic % to about 70 atomic % and aluminum at a concentration of about 30 atomic %. The boundary between adhesion layer 920 and article 910 appeared to be discrete rather than interdiffused.
[0137]
[0156] The amorphous alumina adhesion layer had a thickness of about 60 nm. x F wThe protective coating had a thickness of about 320 nm. As can be further seen by comparing Figures 9C1-9C3, the protective coating composition was uniform throughout the thickness of the coating, except for the surface of the protective coating (about 50 nm thick or about 15% of the coating), where the protective coating exhibited nano-roughness.
[0138]
[0157] 9C1, 9C2, and 9C3 show cross-sectional views of the protective coating observed in FIG. 9A as viewed by scanning electron microscope (SEM) at a 100 nm scale, illustrating the uniformity of the coating thickness and composition, except at the surface of the coating, where nano-roughness is observed.
[0139]
[0158] In particular, Figure 9C1 shows a 100 nm scale SEM image of portion 910C1 of article 910. Portion 910C1 was coated with portion 920C1 of adhesion layer 920. Portion 920C1 had a thickness of approximately 66 nm. Portion 920C1 was coated with portion 930C1 of protective coating 930. Portion 930C1 had a thickness of approximately 340 nm.
[0140]
[0159] In Figure 9C2, a 100 nm scale SEM image of portion 910C2 of article 910 is shown. Portion 910C2 was coated with portion 920C2 of adhesion layer 920. Portion 920C2 had a thickness of about 69 nm. Portion 920C2 was coated with portion 930C2 of protective coating 930. Portion 930C2 had a thickness of about 315 nm.
[0141]
[0160] In Figure 9C3, a 100 nm scale SEM image of portion 910C3 of article 910 is shown. Portion 910C3 was coated with portion 920C3 of adhesion layer 920. Portion 920C3 had a thickness of about 57 nm. Portion 920C3 was coated with portion 930C3 of protective coating 930. Portion 930C3 had a thickness of about 316 nm.
[0142]
[0161] It can be seen that the variation in adhesive layer thickness between portions 920C1, 920C2, and 920C3 is less than about + / - 25%, less than about + / - 20%, or less than about + / - 15%. Additionally, it can be seen that the variation in protective coating thickness between portions 930C1, 930C2, and 930C3 is less than about ±25%, less than about ±20%, less than about ±15%, or less than about ±10%.
[0143]
[0162] Indeed, besides the surface of the protective coating achieving the targeted nano-roughness (according to the embodiment described with respect to FIG. 2B), the protective coating 930 exhibited a uniform thickness and a uniform composition.
[0144] Example 3 - A First Multi-Lamellar Protective Coating Deposited by ALD
[0163] Exemplary herein is crystalline Mg x F w The protective coating has a multi-layer lamellar coating structure of alternating thin layers of amorphous alumina and amorphous alumina. The protective coating was deposited sequentially by ALD. The protective coating in this example was deposited on an amorphous alumina adhesion layer disposed on the surface of the article.
[0145]
[0164] FIGS. 10A1, 10A2, and 10A3 show cross-sectional views of articles coated with multilayer lamellar protective coatings deposited by ALD as viewed by SEM at the 200 nm scale (FIG. 10A1), 100 nm scale (FIG. 10A2), and 20 nm scale (FIG. 10A3).
[0146]
[0165] As can be seen from FIGS. 10A1 and 10A2, the protective coating is made of nine crystalline Mg x F w As can be seen in FIG. 10A3, the crystalline Mg x F w was deposited to a consistent thickness of about 15 nm, and the amorphous alumina layers (excluding the first amorphous adhesion layer) were deposited to a consistent thickness of about 30 nm. The first amorphous alumina adhesion layer had a thickness of about 50 nm.
[0147]
[0166] These figures also show that the boundaries between the surface of the coated article and the adhesive layer, between the adhesive layer and the protective coating, and between the various layers of the multi-lamellar protective coating are discrete and not interdiffused / mixed.
[0148]
[0167] Figure 10B shows an EDS linescan of the protective coating observed in Figures 10A1, 10A2, and 10A3, where section A of the EDS linescan shows the multi-layer protective coating, section B of the EDS linescan shows the adhesive layer, and section C of the EDS linescan shows the coated article.
[0149]
[0168] In section A, the vibration lines of the magnesium (1010), fluorine (1020), oxygen (1030), and aluminum (1040) lines reflect the various layers of the multilamellar protective coating. x F w The layer had a magnesium concentration of about 30 atomic %, a fluorine concentration of about 60 atomic %, and an oxygen concentration of about 10 atomic %. The layer of amorphous alumina had an aluminum concentration of about 25 atomic %, and an oxygen concentration of about 65 atomic %. The total thickness of the protective coating was about 430 nm.
[0150]
[0169] In section B, the amorphous alumina adhesion layer was shown to have an aluminum concentration of about 30 atomic % and an oxygen concentration of about 70 atomic %. In section C, the AlN article was shown to have an N concentration of about 70 atomic % and an Al concentration of about 30 atomic %.
[0151] Example 4 - A second multi-lamellar protective coating deposited by ALD
[0170] Exemplary herein is crystalline Mg x F wThe protective coating has a multi-layer lamellar coating structure of alternating thin layers of amorphous alumina and amorphous alumina. The protective coating was deposited sequentially by ALD. The protective coating in this example was deposited on an amorphous alumina adhesion layer disposed on the surface of the article.
[0152]
[0171] 11A1, 11A2, and 11A3 show cross-sectional views of an article coated with another multilayer lamellar protective coating deposited by ALD according to one embodiment, as viewed by SEM at the 200 nm scale (FIG. 11A1), 100 nm scale (FIG. 11A2), and 20 nm scale (FIG. 11A3).
[0153]
[0172] As can be seen from FIGS. 11A1 and 11A2, the protective coating is made up of six crystalline Mg x F w As can be seen in FIG. 11A3, the crystalline Mg x F w was deposited to a consistent thickness of about 60 nm, and the amorphous alumina layers (excluding the first amorphous alumina adhesion layer) were deposited to a consistent thickness of about 15 nm. The first amorphous alumina adhesion layer had a thickness of about 50 nm.
[0154]
[0173] These figures also show that the boundaries between the surface of the coated article and the adhesive layer, between the adhesive layer and the protective coating, and between the various layers of the multi-lamellar protective coating are discrete and not interdiffused / mixed.
[0155]
[0174] Figure 11B shows an EDS linescan of the protective coating observed in Figures 11A1, 11A2, and 11A3. Section A of the EDS linescan shows the multi-layer protective coating, section B of the EDS linescan shows the adhesive layer, and section C of the EDS linescan shows the coated article.
[0156]
[0175] In section A, the vibrational lines of the magnesium (1110), fluorine (1120), oxygen (1130), and aluminum (1140) lines reflect the various alternating layers of the multilamellar protective coating. x F w The layer had a magnesium concentration of about 30 atomic %, a fluorine concentration of about 60-65 atomic %, and an oxygen concentration of about 5-10 atomic %. The amorphous alumina layer had an aluminum concentration of about 25 atomic %, and an oxygen concentration of about 65 atomic %. The total thickness of the protective coating was about 490 nm.
[0157]
[0176] In section B, the amorphous alumina adhesion layer was shown to have an aluminum concentration of about 30 atomic % and an oxygen concentration of about 70 atomic %. In section C, the AlN article was shown to have an N concentration of about 65-70 atomic % and an Al concentration of about 30-35 atomic %.
[0158] Example 5 - Mg deposited by electron beam ion assisted deposition (EB-IAD) x F w Protective Coating
[0177] 12A1 and 12A2 depict cross-sectional views of an article coated with a 427-438 nm thick protective coating deposited by EB-IAD at a high deposition rate of 1 Å / sec and high ion-assisted deposition as viewed by SEM at the 50 nm and 0.2 μm scales, respectively.
[0159]
[0178] 12B1 and 12B2 depict cross-sectional views of an article coated with a 428-434 nm thick protective coating deposited by EB-IAD at a high deposition rate of 1 Å / sec and low ion-assisted deposition, as viewed by SEM at 50 nm and 0.2 μm scales, respectively.
[0160]
[0179] 12C1 and 12C2 show cross-sectional views of articles coated with a 493-529 nm thick protective coating deposited by EB-IAD at a high deposition rate of 1 Å / sec without ion-assisted deposition, as viewed by SEM at the 50 nm and 0.2 μm scales, respectively.
[0161]
[0180] FIGS. 12D1 and 12D2 show cross-sectional views of articles coated with a 455-488 nm thick protective coating deposited by EB-IAD at a low deposition rate of 0.5 A / sec without ion-assisted deposition, as viewed by SEM at the 50 nm and 0.2 μm scales, respectively.
[0162]
[0181] 12A1-12D2 show that a low IAD provides a more columnar structure of the protective coating, while a high IAD and high deposition rate provide the most uniform, dense, and compact protective coating structure, which may be preferred in certain embodiments.
[0163] Example 6 - Protective coating deposited by EB-IAD over adhesion layer
[0182] FIG. 13 illustrates an SEM view of an amorphous yttrium aluminum garnet (YAG) adhesion layer and a crystalline Mg adhesion layer deposited by EB-IAD according to one embodiment at 0.2 μm scale. x F w
[0023] Figure 1 is a cross-sectional view of an article coated with a protective coating. This example shows that EB-IAD can be successfully used to form a multi-layer protective coating of uniform thickness and composition.
[0164] Example 7 - Chemical resistance of EB-IAD deposited protective layer in NF3 cleaning test
[0183] EB-IAD was used to deposit crystalline Mg on the front and back surfaces of the wafer. x F wA protective coating was deposited. The coated wafers were then subjected to an aggressive cleaning test in which the front side of the wafer was exposed to an NF3 clean at 550°C. After the test, the elemental composition of the center of the front side of the wafer (exposed to NF3 at 550°C) was compared to the elemental composition of the center of the back side of the wafer (not exposed to NF3 at 550°C).
[0165]
[0184] Figure 14 shows that the fluorine concentration on both sides was constant at about 65-70 at.% (F_frontside at 1410, F_backside at 1420), the magnesium concentration on both sides was constant at about 25-30 at.% (Mg_frontside at 1430, Mg_backside at 1440), and the oxygen concentration on both sides was constant at about 6-8 at.% (O_frontside at 1450, O_backside at 1460). The similar composition of the front and back sides of the coated wafers indicates that the coating composition is stable even after NF3 cleaning at 550 °C.
[0166]
[0185] The above description sets forth numerous specific details, such as examples of specific systems, components, methods, and the like, to provide a thorough understanding of some embodiments of the present disclosure. However, it will be apparent to one of ordinary skill in the art that at least some embodiments of the present disclosure can be practiced without these specific details. In other instances, well-known components or methods have not been described in detail or have been presented in simple block diagram form to avoid unnecessarily obscuring the present disclosure. Thus, the specific details described are merely illustrative. A particular implementation can vary from these illustrative details and still be considered to be within the scope of the present disclosure.
[0167]
[0186] As used herein, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Thus, for example, reference to a "precursor" includes a single precursor as well as a mixture of two or more precursors; reference to a "reactant" includes a single reactant as well as a mixture of two or more reactants, and so forth.
[0168]
[0187] References throughout this specification to "an embodiment" or "one embodiment" mean that a particular feature, structure, or characteristic described in connection with that embodiment is included in at least one embodiment. Thus, the appearances of the phrases "in one embodiment" or "in an embodiment" in various places throughout this specification are not necessarily all referring to the same embodiment. Furthermore, the term "or" is intended to mean an inclusive "or" rather than an exclusive "or". When the term "about" or "approximately" is used herein, this is intended to mean that the nominal value presented is accurate within ±10%, such that "about 10" includes 9 to 11.
[0169]
[0188] The recitation of ranges of values herein is merely intended to serve as a shorthand method of referring individually to each individual value within the range, unless otherwise stated herein, and each individual value is incorporated into the specification as if it were individually set forth herein. All methods described herein can be performed in any suitable order, unless otherwise indicated herein or otherwise clearly contradicted by context. The use of any examples or exemplary language (e.g., "etc.") provided herein is intended merely to highlight particular materials and methods, and is not intended to be limiting in scope. No language in the specification should be construed as indicating any non-claimed element as essential to the practice of the disclosed materials and methods.
[0170]
[0189] Although the operations of the methods herein are illustrated and described in a particular order, the order of the operations of each method may be changed such that certain operations can be performed in the reverse order or certain operations can be performed at least in part concurrently with other operations. In alternative embodiments, instructions or sub-operations of separate operations may be performed intermittently and / or alternatingly.
[0171]
[0190] It is to be understood that the above description is intended to be illustrative, and not limiting. Many other embodiments will become apparent to those skilled in the art upon reading and understanding the above description. The scope of the disclosure should therefore be determined with reference to the appended claims, along with the full scope of equivalents to which such claims are entitled.
Claims
1. 1. A semiconductor chamber component comprising: A substrate; a protective coating deposited on the non-roughened surface of the substrate, the protective coating comprising a stack of alternating first and second layers of differing composition, the first layers having a thickness ratio of about 10:1 to about 3:1 relative to the second layers; Including, The protective coating comprises from greater than 2 atomic % to about 25 atomic % oxygen, and the first and second layers of different composition are x F w , M1 x M2 y F w and M1 x M2 y M3 z F w at least one metal fluoride having a formula selected from the group consisting of: a) the metal fluoride is M1 x F w wherein x is 1 and w ranges from 1 to 3; b) the metal fluoride is M1 x M2 y F w wherein x ranges from 0.1 to 1, y ranges from 0.1 to 1, and w ranges from 1 to 3; and c) the metal fluoride is M1 x M2 y M3 z F w wherein x ranges from 0.1 to 1, y ranges from 0.1 to 1, z ranges from 0.1 to 1, and w ranges from 1 to 3; At least one of M1, M2, or M3 comprises magnesium or lanthanum; Semiconductor chamber parts.
2. The protective coating is Mg x F w , La x F w , Y x Mg y F w , Y x La y F w , La x Mg y F w , or Y x Mg y La z F w 10. The semiconductor chamber component of claim 1, comprising at least one of:
3. 10. The semiconductor chamber component of claim 1 further comprising an adhesion and fluorine diffusion barrier layer disposed between said surface of said substrate and said protective coating.
4. The semiconductor chamber component of claim 1 , wherein the protective coating is crystalline.
5. 5. The semiconductor chamber part of claim 4, wherein the top surface of the protective coating has a nano-roughness in the range of about 0.1 microinches to about 200 microinches.
6. 10. The semiconductor chamber component of claim 1, wherein the protective coating has a multi-lamellar structure with alternating amorphous and crystalline layers.
7. The substrate is made of an aluminum alloy, AlN, Al 2 O 3 , Ni, stainless steel, nickel-chromium alloy.
8. The semiconductor chamber component of claim 1 , wherein the substrate comprises an aluminum-based composition.
9. 10. The semiconductor chamber part of claim 1, wherein the substrate is a heater, an electrostatic chuck, a faceplate, a showerhead, a liner, a blocker plate, a gas box, an edge ring, or a bellows.
10. 1. A method for reducing particles during processing in a semiconductor processing chamber, comprising: depositing a protective coating on a non-roughened surface of the substrate by atomic layer deposition (ALD), chemical vapor deposition (CVD), electron beam ion assisted deposition (EB-IAD), or physical vapor deposition (PVD); the protective coating comprises a stack of alternating first and second layers of different composition, the first layers having a thickness ratio of about 10:1 to about 3:1 relative to the second layers; The protective coating comprises from greater than 2 atomic % to about 25 atomic % oxygen, and the first and second layers of different composition are x F w , M1 x M2 y F w and M1 x M2 y M3 z F w at least one metal fluoride having a formula selected from the group consisting of: a) the metal fluoride is M1 x F w wherein x is 1 and w ranges from 1 to 3; b) the metal fluoride is M1 x M2 y F w wherein x ranges from 0.1 to 1, y ranges from 0.1 to 1, and w ranges from 1 to 3; and c) the metal fluoride is M1 x M2 y M3 z F w wherein x ranges from 0.1 to 1, y ranges from 0.1 to 1, z ranges from 0.1 to 1, and w ranges from 1 to 3; At least one of M1, M2, or M3 comprises magnesium or lanthanum; method.
11. The protective coating is Mg x F w , La x F w , Y x Mg y F w , Y x La y F w , La x Mg y F w , or Y x Mg y La z F w The method of claim 10, comprising at least one of:
12. The method of claim 10 further comprising depositing an adhesion and fluorine diffusion barrier layer between the surface of the substrate and the protective coating.
13. 11. The method of claim 10, comprising continuously depositing the protective coating by ALD to achieve a target thickness, the protective coating being crystalline, and depositing adjusts a roughness of a top surface of the protective coating in a range from about 0.1 microinches to about 200 microinches.
14. 11. The method of claim 10, comprising depositing alternating amorphous and crystalline layers by ALD to achieve a multi-layer lamellar structure, each layer being uniform and conformal.
15. The substrate is made of an aluminum alloy, AlN, Al 2 O 3 , Ni, stainless steel, nickel-chromium alloys.
16. The method of claim 10, wherein the substrate is a heater, an electrostatic chuck, a faceplate, a showerhead, a liner, a blocker plate, a gas box, an edge ring, or a bellows.
17. 1. A method for coating a surface of a substrate using atomic layer deposition (ALD), comprising: depositing a first adsorbed layer on the surface of the substrate by pulsing one or more metal precursors of M1, M2, M3, or combinations thereof into an ALD process chamber; 1. A protective coating comprising a stack of alternating first and second layers of different composition, the first and second layers having thicknesses in a ratio of from greater than 2 atomic % to about 25 atomic % oxygen, the first and second layers of different composition comprising: M1 x F w , M1 x M2 y F w , and M1 x M2 y M3 z F w introducing a fluorine component into the ALD processing chamber to form a protective coating comprising at least one metal fluoride having a formula selected from the group consisting of: Including, a) the metal fluoride is M1 x F w wherein x is 1 and w ranges from 1 to 3; b) the metal fluoride is M1 x M2 y F w wherein x ranges from 0.1 to 1, y ranges from 0.1 to 1, and w ranges from 1 to 3; and c) the metal fluoride is M1 x M2 y M3 z F w wherein x ranges from 0.1 to 1, y ranges from 0.1 to 1, z ranges from 0.1 to 1, and w ranges from 1 to 3; At least one of M1, M2, or M3 comprises magnesium or lanthanum; method.
18. 20. The method of claim 17, wherein the introducing step comprises directly fluorinating the first adsorbed layer by pulsing a fluorine-containing reactant into an atomic layer deposition chamber.
19. The introducing step may include pulsing an oxygen-containing reactant into an atomic layer deposition chamber, followed by exposing the oxygen-reacted first adsorbed layer to a fluorine-containing species to fluorinate the oxygen-reacted first adsorbed layer to form a compound of formula M1. x M2 y M3 z F w 20. The method of claim 17, comprising converting said metal fluoride to at least one metal fluoride having the formula:
20. The protective coating is Mg x F w , La x F w , Y x Mg y F w , Y x La y F w , La x Mg y F w , or Y x Mg y La z F w The method of claim 17, comprising at least one of the following:
Citation Information
Patent Citations
Corrosion resistant member and chamber-constituting member
JP2001207275A
Protective Metal Oxyfluoride Coating
JP2019515139A
Erosion-resistant metal fluoride coating deposited by atomic layer deposition method
JP2020012199A
Corrosion resistant coating
US20010051216A1